Pemenuhan Hak-Hak Korban Pelanggaran Berat Hak Asasi Manusia di Indonesia - Bonaventura Pradana Suhendarto (Soegijapranata Catholic University, 2021)
Serious violations of human rights occurred in Indonesia despite Indonesia’s ratification of a number of international human rights law instruments. Victims, including their family and descendants, experiences suffering and loss. Still, there are many victims who haven’t received their rights until now. International law holds states accountable for the victims’ dignity as human beings. This research will examine the fulfillment of the rights of the victims in order to obtain effective and fair remedy and to analyze the application of international human rights law in Indonesia in order to fulfill the rights of the victims of serious violations of human rights. This research was conducted using a sociological juridical approach that collects and analyzes qualitative data. The result shows that the right to truth, the right to justice, the right to reparation and the guarantee of non-repetition are the forms of rights within the framework of transitional justice that must be given to the victims. These rights are interrelated, so they must be fulfilled thoroughly. Indonesia made real efforts to fulfill the rights by establishing a human rights court to resolve the cases of Timor-Timur (East Timor), Tanjung Priok and Abepura. Another effort is made by establishing legal regulations. In fact, Indonesia only recognizes and regulates some rights. The existing legal regulations have not yet encouraged effective implementation, making them difficult to implement. It is necessary to evaluate and re-conceptualize existing legal regulations so that the rights of victims are fully recognized and easy to apply.